2016
DOI: 10.11118/beskyd201609010021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drought and UV radiation impacts on above-ground biomass of mountain grassland by spectral reflectance and thermal imaging techniques

Abstract: Novotná K., Klem K., Holub P., Rapantová B., Urban O. 2016: Evaluation of drought and UV radiation impacts on above-ground biomass of mountain grassland by spectral reflectance and thermal imaging techniques. -Beskydy, 9 (1-2): 21-30Drought represents one of the major factors limiting productivity of managed and natural ecosystems. Under natural field conditions drought is often associated with other stress factors such as high temperature and UV radiation, which may result in enhancement or vice versa allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…For example, although our polytunnels were designed to allow greater air movement than in a fully enclosed structure ( Figure S1 ), less air movement is likely than in an open field, so a given reduction in conductance should increase T leaf to a lesser extent than in a field crop. Nonetheless, our data, and other reports [ 21 , 37 ], suggest that UV-mediated increases in leaf temperature of up to 2°C might commonly occur in crops growing in the field or well-ventilated protected environments.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…For example, although our polytunnels were designed to allow greater air movement than in a fully enclosed structure ( Figure S1 ), less air movement is likely than in an open field, so a given reduction in conductance should increase T leaf to a lesser extent than in a field crop. Nonetheless, our data, and other reports [ 21 , 37 ], suggest that UV-mediated increases in leaf temperature of up to 2°C might commonly occur in crops growing in the field or well-ventilated protected environments.…”
Section: Discussionsupporting
confidence: 57%
“…This need to increase the signal:noise ratio led us to use different approaches to measuring leaf warming under our different experimental regimes. Of course, the same issue of low signal to noise ratio may occur in long-term datasets of mean leaf temperature in the field [ 37 ]. Possibly other researchers have observed leaf warming due to UV exposure, but not reported it due to lack of formal statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, both acted synergistically in order to induce protective mechanisms to reduce the stress in wheat and pea plants. In contrast, Novotná et al (2016), shown that drought led to a significant reduction of above-ground biomass, particularly under ambient UV radiation. Thus, the combined effect of drought and UV radiation which may result in an enhance or vice-versa alleviation of drought impact.…”
Section: Climate Change and Crop Productivity: Impacts And Priority Rmentioning
confidence: 91%
“…164 Osmotic stress-induced upregulation of the UVR8 transcript and protein levels might also contribute to interactive effects of drought and UV-B radiation. 165 This complexity can also be observed in a study where, only in the presence of ambient UV radiation did drought increase canopy temperature and result in decreased accumulation of above-ground biomass in a grassland ecosystem.. 166 Thus, interactive effects of drought and UV-B radiation need to be considered in the context of prevailing and future conditions, particularly warming temperatures. UV radiation and temperature.…”
Section: Plant and Ecosystem Response To Potential Interactive Effectmentioning
confidence: 93%